Political Trust in Post Conflict Society; A Case Study of Aceh - Aryos Nivada (Journal of Political Sphere, 2020)
Public trust on government is a critical issue in post conflict society. As highlighted by Brinkerhoff (2011) and Engvall (2011) that most post conflict societies have low level of trust on government institution that make them prone to face reemergence violent conflict. On the other hand, public trust is pivotal element in fragile society that can strengthen political legitimation of public institutions to enforce the rule of law, ensure public security and deliver public service in post conflict society (Yani, 2015; Blind, 2007; Mishler and Rose, 2005). Based on this argument, it is important to know dynamic of public trust on local and national government in Aceh after a decade of the Helsinki peace agreement have been signed by the government of Indonesia and the Free Aceh Movement. In order to examine this issue, the current study was conducted in survey method with confidence level 95 percent and sampling error 1.07 percent. The researcher interviewed 8340 respondents in 23 districts of Aceh Province in March 2016. The study indicates that Aceh people still have high confidence on government institutions. However, the Acehnese tend to have high level of trust on national government (67.3 percent) and followed by district government (66.7 percent) and provincial government (64.9 percent). In addition, Acehnese also have high confidence on political parties which is around 56 percent. Similarly, Acehnese tend to put more trust on national parties (56.7 percent) rather than local parties (56.4 percent). The result of study shows interesting fact where Acehnese have low level of trust on local parties and local government in which those local institutions led by former Free Aceh Movement activists and combatants. Keywords :Political Trust,Post Conflict Society